The impact of intensive trauma-focused treatment on sexual functioning in individuals with PTSD - van Woudenberg, Clair; Voorendonk, Eline M.; Tunissen, Bo; van Beek, Vince H. F.; Rozendael, Linda; Van Minnen, Agnes; De Jongh, Ad (Frontiers in Psychology, 2023)
Background. Individuals with posttraumatic stress disorder (PTSD) often experience sexual disturbances. Objective. To determine whether intensive trauma-focused treatment is associated with an improvement in sexual functioning (i.e., sexual satisfaction and sexual desire) in individuals with PTSD. Method. In total, 227 patients with PTSD (68.7% women, mean age = 40.97) participated in an intensive eight-day trauma-focused treatment program consisting of prolonged exposure, eye movement and desensitization and reprocessing (EMDR) therapy, physical activity, and psychoeducation. Patients were assessed (i.e., Clinician Administered PTSD Scale and Sexual Functioning Questionnaire) pre- and post-treatment and at 6-months follow-up. Results. Sexual satisfaction and sexual desire increased significantly associated with trauma-focused treatment from pre-treatment to 6-months follow-up, albeit the effect sizes were small (Cohen’s d = 0.39 and 0.17, respectively). Although men reported greater overall sexual desire than women, sexual functioning improved after treatment in both men and women. Furthermore, those with remission of PTSD reported greater sexual functioning post-treatment and at 6-months follow-up, than those without remission. However, changes in PTSD symptoms associated with treatment were not predictive of the level of sexual satisfaction or sexual desire six months after treatment. Conclusion. The results of this uncontrolled study suggest that intensive treatment for PTSD can have beneficial effects on sexual satisfaction and desire in both men and women; however, this may not necessarily be due to a decrease in PTSD symptoms.